Effects of Sparassis latifolia neutral polysaccharide on immune activity via TLR4-mediated MyD88-dependent and independent signaling pathways in RAW264.7 macrophages - Qiao, Zening; Zhao, Yue; Wang, Menghao; Cao, Jinling; Chang, Mingchang; Yun, Shaojun; Cheng, Yanfen; Cheng, Feier; Feng, Cuiping (Frontiers in Nutrition, 2022)
Background: Sparassis latifolia (S. latifolia) is a precious edible fungus with multiple biological activities. To date, no study has been investigated the underlying molecular mechanism of immunoregulation caused by the neutral polysaccharide of S. latifolia. Methods: To investigate immunomodulatory mechanism of S. latifolia neutral polysaccharide (SLNP), SLNP was obtained from S. latifolia and its structure, immune receptors and regulation mechanism were studied. Results: SLNP consisted of arabinose, galactose, glucose, xylose, and mannose with a molar ratio of 6:12:63:10:5. SLNP was a pyran polysaccharide with a relative molecular weight of 3.2×105 Da. SLNP promoted the proliferation of RAW264.7, which further induced the secretions of nitric oxide, TNF-α, IL-6 and IFN-β, and upregulated the immune receptor TLR4 expression. Moreover, SLNP increased remarkably the levels of TRAF6, IRF3, JNK, ERK, p38, and p38 mRNA and protein mediated by TLR4. Conclusion: SLNP regulated the immune function of RAW264.7 through MyD88-dependent and -independent signaling pathways mediated by TLR4 receptor, which suggests that SLNP is a new immunomodulator.